Development of Water Sound Analyzer for An Automatic Fertilizer System in Agriculture Industry - Jailani, Mohamad Hairul Aiman; Mohamad, Khairul Anuar; Alias, Afishah; Nordin, Mohammad Syahmi (Evolution in Electrical and Electronic Engineering, 2022)
Fertigation is a modern agriculture process that allows the right amount of nutrients to the plant compared to traditional approaches. However, the fertigation system used manual mixing of the fertilizer compound with water which may affect the precision of the compound and could affect the growth of a plant. This project developed a water sound classification using Edge Impulse by simulation and modeling and its implementation using Arduino Nano BLE 33 and ESP8266 Wi-Fi module with IoT Blynk platform. In Edge Impulse Studio, the model and simulation for the water sound classification are developed. It was observed to the electrical conductivity (EC) value for nutrients consume by the crops. Moreover, the automatic fertilizer system is wirelessly connected so a user can easily monitor the water level of the fertilizer mixer tank. Finally, the system has shown its potential to provide a new alternative way of controlling a fertigation system.